Effect of Service Quality on Customer Loyalty through Satisfaction, Perceived Value, and Customer Engagements (Study on Indonesian Ride-Hailing Online) - Rachbini, Widarto; Anggraeni, Diana; Febrina, Diah (Advances in Social Sciences Research Journal, 2020)
This study attempted to analyze the effect of service quality on customer’s satisfaction, perceived value, and customer involvement as well as its implications for customer loyalty in Indonesia. The primary data used is the result of questionnaires through an online survey platform with the help of Google Form in July to August 2020. The sampling method was purposive sampling using specific criteria set by the researchers with 300 samples that met the criteria. Data analysis technique used the structural equation models (SEM) with the help of LISREL software. The results showed that there was a significant influence on the quality of Indonesian ride-hailing online services on perceived value, and a significant effect on perceived value on satisfaction as well as a significant effect on customer satisfaction on customer involvement. The only construct which directly influences customer loyalty is customer involvement. This research certainly provides practical advice for the online ride-hailing industry in Indonesia where there are three main suggestions aimed at improving the service quality, satisfaction, customer involvement, and value. Further research is suggested to analyze online ride-hailing in neighboring countries such as Malaysia, Singapore, Vietnam, or other Southeast Asian countries. Keywords: service quality, perceived value, customer satisfaction, customer involvement, customer loyalty and online ride-hailing